Analisa Peningkatan Efisiensi Daya Listrik Runway Edge Light Di Bandar Udara Minangkabau Dengan Lampu LED” - andre saragi; Muhammad Caesar Akbar (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
Runway lighting, namely lights that are installed along the runway (runway) both on the edge and in the middle, Runway lights are also installed at the end of the runway. The function of the runway lights is to provide guidance to pilots on landing and taking off airplanes during the day in bad weather, or at night. In increasing power efficiency so that it is not too large at the Minangkabau airport. Then the replacement of Halogen lamps to LED lamps is carried out in terms of several factors that are more towards the positive side than the negative side, such as from the life time of the lamp, the intensity of the light and the more affordable price. Currently, the Minangkabau airport has not changed the halogen type of runway lights to LED because the economic age factor for the runway facilities at the Minangkabau airport has been fulfilled. One of them is because of the cost, changing the runway lights is quite expensive according to the attachment.